2020
DOI: 10.1071/py20062
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of academic detailing visits on GP knowledge and practice for statin use and management

Abstract: Dyslipidaemia is a major risk factor for cardiovascular disease (CVD) and is routinely managed by GPs. Lipid-modifying medicines, commonly statins, are used to treat dyslipidaemia and prevent CVD in high-risk individuals. A national education program for over 8000 Australian GPs was delivered and evaluated. The program aimed to optimise the use of statins and provide GPs with an Australian-developed statin-associated muscle symptoms (SAMS) management algorithm supporting assessment and management of suspected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…10 The results of this study support findings from other research that used AD to improve practice team knowledge and confidence in BP measurement and hypertension treatment. Hains et al 11 presented similar findings after evaluating a program in Australia that used AD to educate physicians on statin use and management. Compared with the controlled group, they found that the study group reported positive changes after educational intervention.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…10 The results of this study support findings from other research that used AD to improve practice team knowledge and confidence in BP measurement and hypertension treatment. Hains et al 11 presented similar findings after evaluating a program in Australia that used AD to educate physicians on statin use and management. Compared with the controlled group, they found that the study group reported positive changes after educational intervention.…”
Section: Discussionmentioning
confidence: 78%
“…8,9 Previous research shows AD can also be an effective tool for improving cardiovascular care 8,9 and improving BP screening 6 and the use of statins for prevention of cardiovascular disease. 11 Despite AD being an effective and consistent approach to improving physician performance, only one study regarding AD and hypertension within the last 10 years was found, 6 revealing the need for more investigation in this area. This study aimed to use AD to improve clinician and practice team knowledge and confidence in BP management, specifically in lowincome, disadvantaged patient populations.…”
mentioning
confidence: 99%